Teleconsultoria na Atenção Primária de Belo Horizonte: desafios na difusão de uma inovação - Sandra Silva Mitraud Ruas (2012)
INTRODUCTION: Telehealth is the delivery of healthcare services by health professionals who use information and communication technologies for the exchange of information useful for the prevention, diagnosis and treatment of disease, and for continuing health education, research, and evaluation. The goals of the BH Telessaúde Project of the Secretariat of Health of Belo Horizonte are to support healthcare professionals working in primary health care (PHC) and promote the activities of in-service continuing medical education. OBJECTIVES: To determine the rate of adoption, to describe the characteristics of physicians who use offline teleconsultation (TLC), and to identify facilitating factors and barriers to its incorporation into routine work. METHODS: Data related to demographic and professional characteristics of physicians who worked during the period 2006-2010, and data necessary to calculate the rate of use according to parameters of interest were obtained from the BH Telessaúde System, Health Management System computer network, and the electronic portal of Regional Board of Medicine of Minas Gerais. A stratified sample comprised of two men and five women from different municipal health districts who had used the TLC were interviewed individually. A analysis of their comments was performed in order to understand physician attitudes regarding teleconsultation. After reading the transcribed texts of the interviews, excerpts corresponding to each of the categories and subcategories of an explanatory model based on diffusion theory were identified. RESULTS: Utilization rates were 6.0% (2008), 4.8% (2009), and 1.2% (2010); 85 doctors used the TLC service; each physician solicited from 1 to 114 teleconsultations; 57.6% of soliticting physicians were women; ages ranged from 24 to 61 years (median = 40.4 years); 60.0% were family and community medicine specialists, 18.8% internal medicine specialists. The median number of years since graduation and years of service were 14.0 and 6.1 years, respectively. 77.6% were civil service employees. The TLC system was considered to be easy to use, promote professional development, and enhance the doctor-patient relationship. The soliciting physicians affirmed the potential and relevance of TLC for the PHC. The barriers (work overload, weaknesses in training, and limited professional familiarity with computers) interact to influence individual decisions to use the system. Conclusion: The low adoption rate and the contradictions encountered provide clues for guiding the management of actions designed to enhance the system.